REP-BIP: um processo de elicitação de requisitos para projetos de Business Intelligence - MENÉNDEZ, Danielle Amaral (2014)
The requirement elicitation is one of the most important activities of Software Engineering. Understand and correctly specify user expectations is an indispensable condition to ensure that the software goals its intended purpose. For Business Intelligence (BI) projects, requirements elicitation is also an activity of great relevance, since BI projects are based on targeted systems for key areas of organizations, thus errors and defects can produce serious consequences. This work are discussed methods and techniques developed for requirements elicitation activity to present an requirements elicitation process focus on BI projects. The process scope goes from viability study until delivery of the requirements document required for the design phase of the software lifecycle. The proposed process defines phases and activities, interactions between them, a set of input and output documents, as well as the more appropriate elicitation techniques for BI projects. To verify the application of the proposed process and infer its benefits a case study is presented in which its use is made for the development of a BI system in a school environment. The use of the process allowed inferring benefits as an interaction between requirements engineers and stakeholders which allowed it to have a better understanding of elicited needs by technical staff and hence an identification and documentation requirements with higher quality.